Effect of pass and shoot efficiency - Hwang, H. (Journal of Human Sport & Exercise, 2023)
Season rankings in football leagues are affected by the number of goals scored, shots, effective shots, and passes. Extant studies have examined the factors that affect a team`s win or lose, including fewer passes, number of successful passes, more shots, passes in opposition half, scoring efficiency, and pass efficiency. However, the factors that predict and directly affect success in football are diverse and lack consistency. This study thus investigated the factors affecting league rankings in the Italian professional football league, Serie A, and analysed them considering the efficiency of pass and shoot. The analysis confirmed that pass and shoot efficiency significantly affects victory points. Therefore, efficiency can be used as a factor that affects season rankings.